Radiosensitizing effects of miR‐18a‐5p on lung cancer stem‐like cells via downregulating both ATM and HIF‐1α - Xu Chen; Lei Wu; Dezhi Li; Yanmei Xu; Luping Zhang; Kai Niu; Rui Kong; Jiaoyang Gu; Zihan Xu; Zhengtang Chen; Jianguo Sun (Cancer Medicine)
Abstract Lung cancer is one of the main causes of cancer mortality globally. Most patients received radiotherapy during the course of disease. However, radioresistance generally occurs in the majority of these patients, leading to poor curative effect, and the underlying mechanism remains unclear. In the present study, miR‐18a‐5p expression was downregulated in irradiated lung cancer cells. Overexpression of miR‐18a‐5p increased the radiosensitivity of lung cancer cells and inhibited the growth of A549 xenografts after radiation exposure. Dual luciferase report system and miR‐18a‐5p overexpression identified ataxia telangiectasia mutated (ATM) and hypoxia inducible factor 1 alpha (HIF‐1α) as the targets of miR‐18a‐5p. The mRNA and protein expressions of ATM and HIF‐1α were dramatically downregulated by miR‐18a‐5p in vitro and in vivo. Clinically, plasma miR‐18a‐5p expression was significantly higher in radiosensitive than in radioresistant group (P < .001). The cutoff value of miR‐18a‐5p >2.28 was obtained from receiver operating characteristic (ROC) curve. The objective response rate (ORR) was significantly higher in miR‐18a‐5p‐high group than in miR‐18a‐5p‐low group (P < .001). A tendency demonstrated that the median local progression‐free survival (PFS) from radiotherapy was longer in miR‐18a‐5p‐high than in miR‐18a‐5p‐low group (P = .082). The median overall survival (OS) from radiotherapy was numerically longer in miR‐18a‐5p‐high than in miR‐18a‐5p‐low group (P = .281). The sensitivity and specificity of plasma miR‐18a‐5p to predict radiosensitivity was 87% and 95%, respectively. Collectively, these results indicate that miR‐18a‐5p increases the radiosensitivity in lung cancer cells and CD133+ stem‐like cells via downregulating ATM and HIF‐1α expressions. Plasma miR‐18a‐5p would be an available indicator of radiosensitivity in lung cancer patients.